PROSPEK PASAR SAGU - Satria Astana; Hariyatno Dwiprabowo; Triyono Puspitodjati (Jurnal Penelitian Hasil Hutan, 1991)
Based  on  the demand potential,sago starch has  a good prospect in both domestic and international domestic market, sago starch will be largely absorbed by the domestic High Frutose syroupe  (HFS) industry. A new plant of  total capacity as  much as 198.600 tonnes per annum is being considered by the indonesian Government. In interna tional market,  the demand potential  of sago  is promising. The developing countries alone will be facing the cereai, defisit of  67 million tonnes in  1990  and 105  million tonnes in 2000.  Sago starch is expected to contribute a sizeable quantityto overcome  these defisits.